2020
DOI: 10.1371/journal.pone.0225488
|View full text |Cite
|
Sign up to set email alerts
|

Individual housing of male C57BL/6J mice after weaning impairs growth and predisposes for obesity

Abstract: For (metabolic) research models using mice, singly housing is widely used for practical purposes to study e.g. energy balance regulation and derangements herein. Mouse (social) housing practices could however influence study results by modulating (metabolic) health outcomes. To study the effects of the social housing condition, we assessed parameters for energy balance regulation and proneness to (diet induced) obesity in male C57Bl/6J mice that were housed individually or socially (in pairs) directly after we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 76 publications
2
7
0
Order By: Relevance
“…Interestingly, some neuroadaptations produced by HFD treatment parallel those observed with cocaine (see summary in Supplementary Table S2). For example, cocaine exposure produced slight changes in glucose and phospholipid metabolism as well as neurotransmission and increased oxidative stress in the NAc [165,166]. In addition, similar to observations made with HFD treatment [144], cocaine exposure increased oxidative stress and reduced mitochondrial activity in isolated synaptosomes from the whole brain [167].…”
Section: Lack Of Studies On the Sensitivity To Drugs Of Abuse And Dop...supporting
confidence: 52%
See 3 more Smart Citations
“…Interestingly, some neuroadaptations produced by HFD treatment parallel those observed with cocaine (see summary in Supplementary Table S2). For example, cocaine exposure produced slight changes in glucose and phospholipid metabolism as well as neurotransmission and increased oxidative stress in the NAc [165,166]. In addition, similar to observations made with HFD treatment [144], cocaine exposure increased oxidative stress and reduced mitochondrial activity in isolated synaptosomes from the whole brain [167].…”
Section: Lack Of Studies On the Sensitivity To Drugs Of Abuse And Dop...supporting
confidence: 52%
“…Importantly, both the schedule of HFD consumption and the social housing conditions (single- versus group-housed animals) seem to modulate the outcomes of psychostimulant-related behaviours. A recent study suggested that the post-weaning housing condition could modulate the susceptibility to HFD-induced body weight gain, adiposity and thermoregulation in male mice [ 165 ], highlighting the need to consider the housing density in the interpretation of the behavioural and metabolic data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While controls should also be individually housed, this does introduce metabolic and behavioral disruption to the animals. Individual housing of mice has been shown to reduce growth rate while increasing energy intake and expenditure, due in part to maintain thermal neutrality without huddling of litter ( 50 ). Behavioral and endocrine alterations are also noted during individual housing and vary in degree amongst different mouse strains (e.g., BALB/c demonstrate increased anxiety-like behavior versus Swiss Webster which are considered ‘normal’); however, they should be considered when using this model ( 51 ).…”
Section: Preclinical Rodent Models To Study Bone and Relevant Nutriti...mentioning
confidence: 99%